Homogeneity of the photocathode in the Hamamatsu Photomultiplier Tube. (29th November 2021) - Unland Elorrieta, M.A.; Busse, R.S.; Classen, L.; Kappes, A.
Abstract: It is common practice to test the optical properties of photomultiplier tubes (PMTs) by illuminating the entire photocathode region from the front at once and measuring the average performance. However, for optimal utilisation of the PMT performance in experiments, especially in the single-photon region, it is essential to also know the systematic variations across the photocathode, which requires measurements with focused light sources that illuminate only small regions of the PMT. We present a detailed uniformity characterisation of the gain, transit time, transit time spread, and pulse shape of the 80 mm Hamamatsu R15458-02 PMT. We find that the parameters exhibit asymmetry along one axis, likely caused by the position and geometry of the dynode system. For all parameters except the transit time, the observed variations are small given the intrinsic variation of the parameters. For positions with shifted transit time we observe on average underamplified pulses which can potentially be exploited to improve the pulse reconstruction.